Formative Evaluation for a Healthy Corner Store Initiative in Pitt County, North Carolina: Engaging Stakeholders for a Healthy Corner Store Initiative, Part 2 - Pitts, Stephanie B. Jilcott (Centers for Disease Control and Prevention, 2013)
INTRODUCTION: We examined the feasibility of increasing access to healthful food in corner stores to inform a Communities Putting Prevention to Work (CPPW) initiative by engaging stakeholders (corner store owners and customers) in a formative evaluation. METHODS: Qualitative interviews were conducted with corner store owners and managers (n = 11). Customer intercept surveys (n = 179) were also conducted with customers of 9 stores. Corner stores were located in rural food deserts (municipalities without a chain supermarket) and in low-income, urban municipalities in eastern North Carolina. Interviews were transcribed verbatim and double-coded. Qualitative themes related to feasibility of increasing access to healthful foods were extracted. Shopping patterns of rural and urban customers were compared by using t tests. RESULTS: Corner store owners were willing to stock more healthful foods, but they perceived that customer demand for these foods was low. Rural customers reported more frequently shopping at corner stores than urban customers and more frequently stated that the reason they do not eat more fruits and vegetables is that the stores in which they shop do not sell them. Most customers reported they would be very or somewhat likely to purchase fresh produce at a corner store. CONCLUSION: Corner stores may be an important source of food for rural and low-income residents and thus a good place in which to intervene. The results of this formative evaluation were used to plan and evaluate a CPPW healthy corner store initiative.